Colossians and Philemon - Barclay, John M. G. (Sheffield, UK Sheffield Academic, 1997)
Includes bibliographic references and indexes.
Keywords: Bible. N.T. Colossians -- criticism, interpretation, etc; Bible. N.T. Philemon -- criticism, interpretation, etc